A study on knowledge and practice in maternal health care by accredited social health activists of Vijyapaura district, Karnataka, India - Motappa, Rohith; Angadi, Mahabaleshwar (International Journal Of Community Medicine And Public Health, 2020)
Background: One of the key components of national rural health mission was to create a band of female health volunteers, appropriately named “accredited social health activist” (ASHA) in each village within the identified States to act as a bridge between the rural people and health services outlets. They act as health activists in community who will create awareness on health and its determinants, counsel mothers on key healthy behaviors and mobilize the community towards local health planning and increased utilization and accountability of the existing health services. Objectives of the study was to describe the socio-demographic profile of ASHAs working in Vijayapur district and to evaluate the knowledge, attitude, practice of ASHAs towards the maternal care. Methods: A cross-sectional study on 617 ASHAs of Vijayapur district. A pre-designed, semi- structured questionnaire was prepared in English and the interview was conducted in Kannada by explaining them questions one by one. Results: Out of 617 ASHAs interviewed, 427 (69.2%) of them told a pregnant woman should have antenatal care (ANC) visits and 413 (65.3%) ASHAs opined that a minimum of four ANC visits are required. While 542 (87.2%) ASHAs told that they should accompany pregnant woman transport to health centre during labour pains and 570 (92.8%) told that they should stay with the pregnant lady until her delivery is over. Also, it was found that knowledge of ASHAs regarding maternal care was significantly associated with age and duration of service of ASHAs. Conclusions: On the whole, knowledge of ASHAs about care during pregnancy and care of new-born was considerably good.